Processo produtivo de instalações provisórias de madeira para canteiros de obras - Souza, Fernando Braga de (2016)
A temporary work environment containing areas of support to the production process, such as the administrative, operational, and living areas should be foreseen and planned as support to the implementation of works. These types of facilities are very common in sites and their planning is as important as the provision of the physical flow of materials necessary to the execution of the services. However, the way this is designed not always follows the laid down rules that add productivity to the process. Nor does it meet the diversity of existing typologies for the design of interim facilities. Currently, there are specific industrial constructive systems developed for provisional installations with a focus on integration between assembling and disassembling procedures, and in the reuse and recycling of components. The incorporation of BIM (Building Information Modeling) technology in the Brazilian market currently has an emphasis on the design phase for buildings due to its consolidated advantages. However, this work supports the use of BIM for the design of temporary construction site installations. In this sense, the general objective of this research was to analyze the production process of provisional facilities industrialized in wood. The feasibility of using BIM concepts also for this type of project, enabling the aggregation of this methodology benefits is thus presented as a specific objective. Through the Case Study method, the field research is presented, containing reports of visits to two plant manufacturers, follow-up of two works, and proposition of a 4D virtual model simulating the phases of fabrication, assembly, and disassembly. The results indicated that the production process of provisional facilities could be improved with minor changes and also that it is possible to have benefits in the use of BIM for drafting, design, and simulation of assembly and disassembly. The tool obtained can be used for the implementation planning and also for training of workers. It was found that suppliers offer the opportunity to reuse industrialized facilities, helping to reduce waste and costs and to promote sustainability.